2004
DOI: 10.1038/sj.leu.2403458
|View full text |Cite
|
Sign up to set email alerts
|

A distinctive nuclear morphology in acute myeloid leukemia is strongly associated with loss of HLA-DR expression and FLT3 internal tandem duplication

Abstract: In a 5-year survey of nonpromyelocytic/nonmonocytic acute myeloid leukemias (AMLs) diagnosed in the University of Washington Hematopathology Laboratory, we identified 19 cases containing distinctive, cup-like nuclear indentation in 10% or more of the blasts ('AML-cuplike'). Fourteen of these cases (74%) demonstrated near-complete loss of HLA-DR expression, while the other five cases showed partial loss of HLA-DR. A total of 16 of the cases (84%) demonstrated internal tandem duplication (ITD) of the Flt3 gene. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 20 publications
6
54
0
Order By: Relevance
“…Therefore we used a cut-off of ≥5% blast cells with typical morphology in blood and/or bone marrow for the definition of cup-like AML for the statistical analyses, which was lower than in the studies by Kussik et al 2 and Chen et al 3 The phenomenon seemed to be more pronounced in the peripheral blood and this was in line with the higher median percentage of cup-like positive blast cells in this group. Whether there really are more cup-like cells in the PB, or whether the phenomenon is induced by preparing the smears, remains hypothetical.…”
Section: Resultsmentioning
confidence: 71%
“…Therefore we used a cut-off of ≥5% blast cells with typical morphology in blood and/or bone marrow for the definition of cup-like AML for the statistical analyses, which was lower than in the studies by Kussik et al 2 and Chen et al 3 The phenomenon seemed to be more pronounced in the peripheral blood and this was in line with the higher median percentage of cup-like positive blast cells in this group. Whether there really are more cup-like cells in the PB, or whether the phenomenon is induced by preparing the smears, remains hypothetical.…”
Section: Resultsmentioning
confidence: 71%
“…The previously described cup-like morphology has been reported to be associated with NPM1 mutations, 4 with FLT3-ITD and with a lack of HLA-DR expression; 10 however, again no complete correlations were observed.…”
Section: Mll-ptdmentioning
confidence: 62%
“…Especially, 10% of non-APL patients were negative for both CD34 and HLA-DR [17]. One author reported that invaginated nuclear morphology was associated with loss of HLA-DR and CD34 expressions in non-APL [19]. These results suggested that absence of HLA-DR antigen was accompanied by absence of CD34 antigen in AML.…”
Section: Disussionmentioning
confidence: 66%